(untitled) (Research, Society and Development, 2022)
Introduction: Obstetric Brachial Palsy (OBP) generates losses in functionality and quality of life of children. Physiotherapeutic intervention in these cases has the objective of recovering the functional capacity of the limb and having a positive impact on quality of life. Objective: To describe the most used techniques in physiotherapy performance for the treatment of PBO through an integrative review. Methodology: This is a literature review through a bibliographic survey in the electronic databases National Library of Medicine (PubMed), Scientific Electronic Library Online (Scielo), Cochrane Library, articles and books on Academic Google with a focus on the theme. Using the following descriptors: Brachial Plexus neoropathies AND neonatal brachial plexus palsy OR Child AND Pediatrics OR Physiotherapy AND Rehabilitation. Results: 171 studies were identified, of which only four were included in this review. In the reviewed studies, the interventions had significant effects that resulted in improved strength, range of motion, greater ability to use the affected upper limb, functional gains, and gains in skills to perform bimanual tasks. Conclusion: The physical therapy treatment brought significant gains for children diagnosed with PBO. Physiotherapeutic interventions are essential to promote the function of the affected limb, in order to provide quality of life and prevent deformities.